Environment Material in Science Learning Using Problem Based Learning Model with the SETS Approach in Terms of Students’Activities and Learning Outcomes (Universitas Negeri Semarang, 2021)
This research is aimed to analyze science learning that applies the PBL model with the SETS approach of students’ activities and learning outcomes. The research methodology used pre-test and post-test group design with each one of experimental and control classes. The findings obtained by an average gain score of the experimental class 0.2895 and the control class 0.2135, so that the experimental class has an increase in learning outcomes higher than the control class. The category of students who were very active and active in the experimental class was higher with a percentage of 87%. The conclusion of the study was the science learning model applying the PBL model with the SETS approach can optimize students’ activities and learning outcomes.